Structure-dependence and metal-dependence on atomically dispersed Ir catalysts for efficient n-butane dehydrogenation - Xiaowen Chen; Xuetao Qin; Yueyue Jiao; Mi Peng; Jiangyong Diao; Pengju Ren; Chengyu Li; Dequan Xiao; Xiaodong Wen; Zheng Jiang; Ning Wang; Xiangbin Cai; et al. (Nature Communications, 2023)
Abstract Single-site pincer-ligated iridium complexes exhibit the ability for C-H activation in homogeneous catalysis. However, instability and difficulty in catalyst recycling are inherent disadvantages of the homogeneous catalyst, limiting its development. Here, we report an atomically dispersed Ir catalyst as the bridge between homogeneous and heterogeneous catalysis, which displays an outstanding catalytic performance for n-butane dehydrogenation, with a remarkable n-butane reaction rate (8.8 mol·gIr −1·h−1) and high butene selectivity (95.6%) at low temperature (450 °C). Significantly, we correlate the BDH activity with the Ir species from nanoscale to sub-nanoscale, to reveal the nature of structure-dependence of catalyst. Moreover, we compare Ir single atoms with Pt single atoms and Pd single atoms for in-depth understanding the nature of metal-dependence at the atomic level. From experimental and theoretical calculations results, the isolated Ir site is suitable for both reactant adsorption/activation and product desorption. Its remarkable dehydrogenation capacity and moderate adsorption behavior are the key to the outstanding catalytic activity and selectivity.